Patients’ waiting experiences and satisfaction with oral care delivery at two levels of care in Ibadan, Nigeria (2018)
Background: Patients waiting experiences at the dental centre and their satisfaction with services rendered by the health care team have not been fully explored and may be important factors that have influenced the pattern of utilization of dental services in this part of the world. The aim of this study was to determine what patients’ waiting experiences are, at two dental centres and find out how satisfied patients were with the services provided. Methods: A cross sectional study was conducted at two dental centres in Ibadan, Oyo State, Nigeria over a period of twelve months. Data was collected using a 29-item structured questionnaire. Information sought were patients’ biodata, reasons for presenting at the dental centre, time on entry into the centre, their experiences from point of entry into the dental centre to consultation with the dentist and how satisfied they were with the services rendered. Data were analyzed using SPSS version 22. Results: Two hundred and sixty-six respondents participated in the study with a mean age of 36.3 ± 17years. The mean waiting time at the Primary Oral Health Care Center (POHCC) and tertiary health centre (UCH) were 11.5 ± 17.0 and 102.3 ± 47.3 minutes respectively. Many (85.3%) were satisfied with the services offered by the dentist, 78.0% were comfortable while waiting to see the doctor. Patients attending the POHCC were more satisfied with the stage of dropping appointment cards but less satisfied with the stage of being called in to see the doctor (22.9%) and when with the doctor (20.6%) compared with patients attending UCH (13.3%)(p<0.005). Conclusion: Many patients were comfortable while waiting to be seen by the dentist and the majority were satisfied with the stages of service delivery. However, causes of dissatisfaction and discomforts experienced by some of the patients will have to be addressed.